Costos de producción en el cultivo de arroz de la Arrocera Caicedo del sector La Pradera cantón Montalvo en el período 2021. - Mastian Sisa, Joselin Estefanía (2022)
This case study was carried out in Arrocera Caicedo, a trade name assigned by its owner despite the fact that it does not appear in the Single Taxpayer Registry, it began its activities on March 13, 2000 and is legally registered in the Revenue Service. Internal. It has various economic activities, its main one being rice cultivation, including organic cultivation and genetically modified cultivation. It is located in the Pradera Canton Montalvo Sector. In the development, the production costs that intervene in the cultivation of rice are described, in addition to the problems that arose as it is: the rise in production costs, especially the increase in the prices of agricultural inputs, due to triggers that arose in Europe and Asia. This investigative work has as a research subline Financial, tax and social commitment management. Likewise, the descriptive and documentary methodology will be used to collect pertinent and effective information. The importance of this work is rooted in determining the production costs of the Caicedo Rice Cooker during the accounting period 2021 in order to know the utility of the fiscal year.